2009
DOI: 10.1021/ja902087t
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Monomer−Template Complexation: An Explanation for Molecularly Imprinted Polymer Recognition Site Heterogeneity

Abstract: We here present the first simulation of a complete molecularly imprinted polymer prepolymerization system. Molecular dynamics studies were performed for a system comprising a total of 1199 discrete molecules, replicating the components and concentrations employed in the corresponding polymer synthesis. The observed interactions correlate well with results obtained from (1)H NMR spectroscopic studies. Comparison with simulations performed in the absence of cross-linking agent (ethylene dimethacrylate) demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 65 publications
4
108
0
Order By: Relevance
“…Recently, Karlsson et al [39] have addressed the importance of various possible interactions within the prepolymerization mixture, such as monomer…monomer and template…template self-association. In our studied systems, only the monomers prefer to self-associate through intermolecular hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Karlsson et al [39] have addressed the importance of various possible interactions within the prepolymerization mixture, such as monomer…monomer and template…template self-association. In our studied systems, only the monomers prefer to self-associate through intermolecular hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…One particular complication appears to be the problems that can arise from the lack of an explicit solvent [44,45]. For electronic structure methods, the inclusion of a reasonable number of solvent molecules makes the calculation rather time-consuming; as a result, solvent effects are often omitted completely.…”
Section: Electronic Structure Methodsmentioning
confidence: 99%
“…By also including the initiator and multiple templates in correct stoichiometries to represent an actual pre-polymerization system, Karlsson et al [45] were able to present a comprehensive investigation of all non-covalent interactions taking place in a bupivacaine imprinting procedure. Interestingly, the authors reported both a correlation between results obtained from a series of NMR spectroscopic studies on monomer-template complex stability and simulated data, and also the origin of the recognition-site heterogeneity frequently demonstrated in MIPs (see Fig.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…[22], with permission from The Royal Society of Chemistry can conducted by experimental or computational methods [37][38][39][40]. For protein imprinting, the monomer should be soluble in a polar solvent, ideally in water, because most proteins do not dissolve in nonpolar or medium polarity solvents.…”
Section: Rational Design Of Protein-imprinted Materialsmentioning
confidence: 99%